2011
DOI: 10.1089/pho.2010.2925
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Structural Changes on Human Dental Enamel After Er:YAG Laser Irradiation: AFM, SEM, and EDS Evaluation

Abstract: Objective: The purpose of this study was to evaluate, using atomic force microscopy (AFM), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS), the morphological and structural changes of the enamel after irradiation with the Er:YAG laser. Background data: A previous study showed that subablative Er:YAG laser irradiation produced undesirable morphological changes on the enamel surface, such as craters and cracks; however, the enamel acid resistance was not increased. Methods: Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 27 publications
(51 reference statements)
4
41
0
3
Order By: Relevance
“…Other studies also indicated topographical alterations including irregularities, craters and cracks in enamel and dentin specimens treated by Er:YAG or Er,Cr:YSGG lasers. 10,11,[20][21][22][23]30,33 The laser settings used in this study were selected in order to produce efficient enamel and dentin ablation, simulating the clinical conditions. Most of the previous studies used lower pulse repletion rates compared to that used in this study, but the number of microexplosions and the rate of ablation are directly dependent on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also indicated topographical alterations including irregularities, craters and cracks in enamel and dentin specimens treated by Er:YAG or Er,Cr:YSGG lasers. 10,11,[20][21][22][23]30,33 The laser settings used in this study were selected in order to produce efficient enamel and dentin ablation, simulating the clinical conditions. Most of the previous studies used lower pulse repletion rates compared to that used in this study, but the number of microexplosions and the rate of ablation are directly dependent on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated in previous studies that high level of energies increased dentin microhardness in the deepest area of the cavity until 60  μ m [31]. Consequently, the shear bond strength, in surfaces with lower energy density, was high due to fewer morphologic changes [32]. Bonding self-adhering flowable resin composite to laser irradiated dentin still remains a challenge because of the lack of information about alterations in collagen fibrils and mineral content promoted by Er:YAG laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between the tip and the sample was 1 mm, which was ensured by using a sheet of stainless steel (23 mm × 5 mm × 0 5 mm) that was fixed to the top of the laser handpiece. At this tip-sample distance, the exit tip and the laser beam had the same diameter, which was confirmed by a laminated infrared sensor screen (Lumitek International Inc., Ijamsville, MD, USA) [18,25,27,28]. Each sample was irradiated only once for 20 sec.…”
Section: Er:yag Lasermentioning
confidence: 94%
“…The crown was fixed to a glass slide with thermoplasticized epoxy resin (Allied, Rancho Dominguez, CA). Afterwards, a diamond wheel (South Bay Technology Inc.) was employed to obtain samples under constant irrigation [18,25,27,28].…”
Section: Tooth Selection and Sample Preparationmentioning
confidence: 99%